CD14loCD301b+ macrophages gathering as a proangiogenic marker in adipose tissues - Lv, Yibing; Zheng, Yidan; Su, Shanshan; Xiao, Junyi; Yang, Jie; Xiong, Lingyun; Guo, Yanyan; Zhou, Xiaoqi; Guo, Nengqiang; Lei, Ping (Journal of lipid research, 2025)
The role of the monocyte marker CD14 in the regulation of obesity is increasingly recognized. Our observations indicated that Cd14−/− mice exhibited a leaner body shape compared to their wild-type (WT) counterparts. And the loss of CD14 alleviated high-fat diet–induced obesity in mice. In human subjects, CD14 level was tested to be positively correlated with overweight and obesity. However, the relationship between CD14 and the development of obesity remains only partially understood. To investigate the underlying mechanisms, adipose tissues (ATs) from Cd14−/− and WT mice were subjected to deep RNA sequencing. Gene Ontology enrichment analysis revealed a significant enhancement of angiogenesis-related function in the Cd14−/− epididymal adipose tissues compared to WT counterpart, which was accompanied by an upregulation of Cd301b. Subsequent assays confirmed the enhanced angiogenesis and more accumulation of CD301b+ macrophages in Cd14−/− epididymal adipose tissues. Because Igf1 expression has been suggested to be associated with Cd301b expression through pseudotime analysis, we found it was insulin-like growth factor 1 secreted from Cd14−/− macrophages that mediated the angiogenesis enhancement. Collectively, our ﬁndings indicate that CD14 deficiency increased the accumulation of CD14loCD301b+ macrophages in ATs, which may serve as a proangiogenic marker, providing novel insights into the relationship between CD14 and obesity development.